Assessment of Knowledge, Attitude and Practice about Self Medication among Rural Areas in Erode District - K, Sivasakthi; KS, Koshila; Mohammed K, Sajeer; S, Viswa (Indian Journal of Pharmacy Practice)
Background: In India, it is very common to observe self-medication practice, which is emerging as a challenge to health care providers. Few studies were conducted at community level in rural India to assess the magnitude of self-medication practices. Aim: This study aims to assess the awareness of self-medication practices and attitude among rural areas in Erode district. Materials and Methods: A Cross sectional study was conducted with a self-directed survey based questionnaire among 150 people who held permanent residence in rural areas in Erode district with different socio-economic backgrounds from the age group of 20 to 50 yrs. Results: Among the 150 samples, the maximum study sample lies in the age category between 20-30 years, 53.33% were men and 46.67% were women, 28.67% of people were graduate. The most common reason for self-medication was doctor’s clinic far from home (22.39%) and doctor’s fee (22.34%). The most common symptoms used for head ache (22.01%) and fever (16.77%).87% of people take self-medication under the source of pharmacy shop. Over 90% of people saw the information at the time of taking self-medication but only 40% of people should understand the information partially. Commonly used medicines were analgesics (44%) and antibiotics (42%). Conclusion: Self-medication is a global phenomenon. Study reveals that with increasing the literacy, the demand of self-medication also increasing day by day. So that pharmacists and other healthcare professionals should make the awareness to the public about self-medication.
Keywords: Self-medication; Literacy; Pharmacist; Awareness; Appropriate use.